Implications for and from Chronicles - Mitchell, Christine (The journal of Hebrew scriptures, 2005)
This conversation with W. M. Schniedewind, How the Bible Became a Book: The Textualization of Ancient Israel includes the following contributions: David M. Carr, “Response to W. M. Schniedewind, How the Bible Became a Book: The Textualization of Ancient Israel.” Tamara Cohn Eskenazi, “Implications for and from Ezra-Nehemiah.” Christine Mitchell, “Implications for and from Chronicles.” William M. Schniedewind, “Adrift: How the Bible Became a Book.” The conversation began at an SBL session devoted to the book. The contributors developed and revised their oral comments. W. M. Schniedewind responds to them.